Modeling the determinants of poverty in Zimbabwe - Pindiriri, Carren (International Food Policy Research Institute, 2015)
Many poverty profiles classifying the poor according to characteristics such as level of education, consumption levels, employment status, and household size have been constructed in Zimbabwe (see Malaba, 2013). However, despite their usefulness in summarizing poverty information and providing clues to possible determinants of poverty, these profiles are restricted by the bivariate nature of their clarifications (Datt and Jolliffe, 1999). This article extends Zimbabwe’s poverty profiles into a poverty determinants model, with the overall objective of examining the impact of household characteristics on household poverty. The findings show that poverty measures in Zimbabwe have been understated by previous studies due to the absence of data weighting and endogeneity. Poverty in Zimbabwe is primarily caused by low household income, low educational achievement of the household head, bigger household size, and household location. The possible endogeneity of household size was controlled for in order to improve the robustness of the results. This article recommends, among other things, increasing family planning campaigns, supporting education for the poor, creating employment through implementing investment-friendly policies, and establishing land redistribution policies targeting the poor.